2009
DOI: 10.1002/adma.200802748
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Bottlenecks of Bioreactors in 3D Cell Culture and Tissue Manufacturing

Abstract: Over the last decade, we have witnessed an increased recognition of the importance of 3D culture models to study various aspects of cell physiology and pathology, as well as to engineer implantable tissues. As compared to well-established 2D cell-culture systems, cell/tissue culture within 3D porous biomaterials has introduced new scientific and technical challenges associated with complex transport phenomena, physical forces, and cell-microenvironment interactions. While bioreactor-based 3D model systems have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 124 publications
(138 reference statements)
0
49
0
Order By: Relevance
“…51 Though a greater level of biological understanding of how cells respond to different surfaces is currently missing, the application of modern 'omics' techniques such as transcriptomics and proteomics to well understood model systems such as those described in this contribution will increase our understanding further and advance the development of materials that can influence growth, differentiation and selection in a controlled manner through the properties they exhibit.…”
Section: 23mentioning
confidence: 99%
“…51 Though a greater level of biological understanding of how cells respond to different surfaces is currently missing, the application of modern 'omics' techniques such as transcriptomics and proteomics to well understood model systems such as those described in this contribution will increase our understanding further and advance the development of materials that can influence growth, differentiation and selection in a controlled manner through the properties they exhibit.…”
Section: 23mentioning
confidence: 99%
“…In addition, initial cell distribution in a scaffold is strongly related with the final tissue properties. 5,8 Since human cells are often available in short supply, 9 maximization of the cell-seeding process is necessary. Studies on seeding efficiency by static deposition have reported results ranging from 18% to 85%.…”
mentioning
confidence: 99%
“…3,10,11,15 The main challenge of dynamic cell seeding is the proper selection of parameters. 9,16 On this topic, Wendt et al 3 concluded that for oscillating perfusion, high fluid flow velocities were detrimental for cells to adhere to the material, but for extremely low velocities, the cells did not move (static regime)-hence the importance to optimize fluid flow rate.…”
mentioning
confidence: 99%
“…54 There are growing data to show that the use of dynamic culture or fluid mixing can be optimized to modulate the spatial heterogeneity of engineered menisci as well as the correlated mechanical properties. [55][56][57] Compressive deformation or hydrostatic pressure has been shown to enhance the structure and function of engineered meniscus tissues. [58][59][60] Dynamic compression of constructs based on microchanneled scaffolds resulted in aligned cell layers and collagen fibers, 58 whereas hydrostatic pressure combined with TGF-b1 increased collagen and glycosaminoglycan deposition by meniscus cells, ultimately leading to enhanced compressive properties.…”
Section: Biological Augmentation and Tissue Engineering Approaches Inmentioning
confidence: 99%